Workshop Analisis Kristalografi Dengan Metode Rietveld Menggunakan Aplikasi X’Pert Highscore - Ramadian Ridho Illahi; Arif Budianto; Zahrah Ramadlan Mubarokah; Dian W. Kurniawidi; Siti Alaa; Teguh Ardianto; Susi Rahayu (Universitas Mataram, 2023)
Final year students are required to have the ability to innovate, be creative, have personality, and develop independence in seeking and finding knowledge through realities and field dynamics such as ability requirements, real problems, social interaction, collaboration, self-management, as well as performance demands and achievement targets. In order for students' hard skills and soft skills to be formed strongly, it is felt necessary to provide additional skills, especially those that support the completion of the Final Project. Workshops on the use of the Originlab are quite urgent in research so as to speed up the completion of the Final Project (Thesis) for students interested in Materials. This software is commonly used to prepare XRD, FT-IR, UV-Vis and other spectra that are quite important in materials. In this explanation, a brief description of the XRD data preparation steps is described, starting from data input to quantitative and qualitative data analysis. Data analysis was carried out including determining the value of particle size, FWHM, crystal structure and lattice strain. Workshop participants totaled 20 students and were held for 7 days, from 7 to 15 May 2023 with details of 2 days offline, 1 day online via G-Meet and 4 days of mentoring.